(untitled) (Bangladesh Journal of Child Health, 2018)
Background: Despite widespread vaccination against measles in Bangladesh outbreak continue to occur. The Objective of the study was to see the demographic characteristics of patients who had the diagnosis of measles at Dhaka Shishu (Children) Hospital and occurrence of measles from the time of vaccination. Methodology: This retrospective study was conducted on patient who were diagnosed as measles at Dhaka Shishu (Children) Hospital between 1st January 2017 to 30th April 2017. The diagnosis of measles based on clinical features and laboratory confirmation. Demographic characteristics of patients and occurrence of measles from the time of vaccination was recorded. Data were analyzed by using SPSS version 21. Results: Total 13864 patients were admitted during the study period and among them 23 were confirmed as measles. Rate of measles was found as 0.16% among hospitalized children with male predominance. Among the measles patients age of onset was <9 months in 2(8.7%), 9-12 months in 8(34.8%), 13-14 months in 11(47.8%) and 15 months and above in 2(8.6%) cases. Among 23 measles patients vaccine was not given in 2(8.7%) patients, one dose of vaccine was given in 19(82.60%) patients and two doses of vaccine were given in 2(8.7%) patients. Most of the measles patients came after one vaccination which means after first dose. Though measles incidence significantly reduced after the successful introduction of measles vaccination in EPI, still measles are prevalent in our country and occurs before completion of two doses of vaccine. Conclusion: Majority of measles cases developed before completion of two doses of vaccine though the successful measles vaccination are going on. Bangladesh J Child Health 2018; VOL 42 (1) :15-18